The influence of the sports of specialization of various types on the electrical activity of the cortex - Іванюк [Olga Ivaniuk] Ольга Андріївна (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Studied electrical activity of the cortex in the alpha range of the еlectroencephalography (EEG) in right-handed young men, who are engaged in аcyclic and cyclic sports. Revealed the presence of stable characteristics of the spatial organization of cortical processes in athletes during the execution of cognitive tasks. It was found that the spatial distribution of coherent links between the parts of the brain depends on the sport of specialization of different types. In the group of sportsmen of cyclic sports, to play the information from the memory noted more pronounced decrease in alpha range of the EEG between the frontal, central, temporal and occipital areas of the cerebral cortex, compared with the athletes of acyclic sports. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>